Q-CARE-VLC: Quantum-Secured Vehicular Visible-Light Communication with Key-Continuity-Aware Handover for Smart-Ambulance Healthcare - Vivek Kumar; Keshav Kumar; Mohit Kumar Srivastava; Abhishek Rathour; Gaurav Sahu (International Journal of Computer Information Systems and Industrial Management Applications, 2026)
Transmission of patient telemetry, diagnostic video, electronic health records, and emergency-control information from a moving ambulance requires simultaneous low latency, high reliability, and strong confidentiality. Vehicular visible-light communication (V-VLC) offers a directional high-rate optical channel, but classical key exchange remains exposed to long-term cryptanalytic risk, and quantum key distribution (QKD) is difficult to sustain under mobility because the quantum link is sensitive to range, background light, pointing error, and handover interruption. This paper proposes Q-CARE-VLC, a dual-plane quantum-secured V-VLC architecture for connected ambulances. The architecture combines a high-rate classical vehicle-to-infrastructure (V2I) VLC data plane with a co-aligned decoy-state BB84 quantum key plane, trusted roadside quantum-VLC units (QVUs), a hospital key orchestrator, a dual-aperture make-before-break quantum handover mechanism, and a priority-aware quantum-key buffer. A unified analytical model is developed for vehicular optical attenuation, atmospheric loss, pointing jitter, classical achievable rate, quantum bit error rate (QBER), asymptotic decoy-state secret-key rate (SKR), key-buffer dynamics, handover interruption, and deadline-constrained medical traffic. A quantum-key-aware handover and scheduling policy gives critical physiological traffic precedence while pre-acquiring keys from the next QVU before the active quantum session is released. Monte Carlo and time-slotted simulations over a 4-km urban emergency corridor, in which all schemes share one simulator and one physical-layer parameter set, show that at an aggregate key-refresh demand of 75 kb/s, Q-CARE-VLC maintains 100% quantum-secure service continuity compared with 80.16% for a static-buffer QKD baseline and 78.77% for break-before-make QKD. At 80 km/h the modeled handover interruption fraction falls from 6.25% to 0.42%. For a daytime clear-air link, the modeled SKR is 70.62 kb/s at 40 m and 13.96 kb/s at 80 m, while the classical VLC plane remains above 83 Mb/s at 80 m. Under an 80 Mb/s aggregate medical load, the proposed scheduler satisfies the 20-ms critical-traffic deadline in 100% of slots, whereas a direct-QKD/FIFO baseline reaches only 12.69%. The results are obtained from a calibrated simulation study rather than a hardware prototype, and they establish a vehicular-healthcare architecture in which quantum key generation, mobility management, and clinical traffic prioritization are co-designed rather than treated as independent functions.